2021
DOI: 10.51372/bioagro341.7
|View full text |Cite
|
Sign up to set email alerts
|

Una alta diversidad de hongos micorrízicos arbusculares influye en la absorción de cadmio y crecimiento vegetal del cacao

Abstract: El cadmio (Cd) en el suelo es un problema en las plantaciones de cacao en el Perú. El objetivo de este estudio fue evaluar el efecto de la diversidad de hongos formadores de micorrizas arbusculares (HMA) provenientes de diferentes provincias de la Amazonía peruana en la absorción de cadmio y en el crecimiento vegetativo del cacao en condiciones de vivero. Se inocularon semillas germinadas con diferentes especies de HMA, a razón de 1500 esporas, en sustratos constituidos por un volumen de arena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…This coincides with Wu et al (2016), whom show negative effects of Cd (and Pb) toxicity on AMF and root endophytic fungi associated with wheat. Similar negative effects were shown by Vallejos-Torres et al (2022) in cacao plants. Plant height and root length were higher under AMF, compost, and AMF + compost treatments, but were negatively affected by Cd application, as roots are the main way in which Cd enters to the plant, hindering its growth (Kanu et al, 2017).…”
Section: Effects On Plant Growth and Chlorophyllsupporting
confidence: 78%
See 2 more Smart Citations
“…This coincides with Wu et al (2016), whom show negative effects of Cd (and Pb) toxicity on AMF and root endophytic fungi associated with wheat. Similar negative effects were shown by Vallejos-Torres et al (2022) in cacao plants. Plant height and root length were higher under AMF, compost, and AMF + compost treatments, but were negatively affected by Cd application, as roots are the main way in which Cd enters to the plant, hindering its growth (Kanu et al, 2017).…”
Section: Effects On Plant Growth and Chlorophyllsupporting
confidence: 78%
“…The AMF inoculum consisted of 2000 spores isolated from the Mariscal Cáceres Province in the San Martín region, Peru. The mycorrhizal inoculum was composed of a mixture of spores of the following species: Claroideoglomus sp., Microkamienskia peruviana, Microkamienskia sp., Diversispora sp., and Claroideoglomus etunicatum (Vallejos-Torres et al, 2022).…”
Section: Experimental Designmentioning
confidence: 98%
See 1 more Smart Citation
“…The pH in the study plots was slightly-acid to neutral (between 5.55 and 6.71), an important factor since the mobility and availability of Cd in the soil is mainly controlled by soil pH (Alloway, 2013). The overall low Cd content in our study could also be explained by the use of compost, as this material has been shown to reduce or immobilize Cd (Vallejos et al, 2022). Regarding Cd content in leaves (higher in monoculture systems; Figure 2c), our results are consistent with those of Gramlich et al (2017), who reported lower Cd contents in cacao leaves from agroforestry systems in the Alto Beni region, Bolivia, compared to leaves from monocultures.…”
Section: Discussionmentioning
confidence: 64%
“…Algunos estudios han demostrado que los HMA pueden disminuir la concentración de Cd en las plantas (Vallejos-Torres et al, 2021) al aumentar su biomasa. Como se presenta en este estudio, el crecimiento de las plantas de girasol y su biomasa aumentaron significativamente en los tratamientos que presentaban HMA y altas concentraciones de Cd, lo que concuerda con lo indicado por Janeeshma y Puthur (2020).…”
Section: Discussionunclassified